Neural circuits that drive startle behavior, with a focus on the Mauthner cells and spiral fiber neurons of fishes. (2nd April 2016) - Hale, Melina E.; Katz, Hilary R.; Peek, Martin Y.; Fremont, Rachel T.
ABSTRACT: Startle behaviors are rapid, high-performance motor responses to threatening stimuli. Startle responses have been identified in a broad range of species across animal diversity. For investigations of neural circuit structure and function, these behaviors offer a number of benefits, including that they are driven by large and identifiable neurons and their neural control is simple in comparison to other behaviors. Among vertebrates, the best-known startle circuit is the Mauthner cell circuit of fishes. In recent years, genetic approaches in zebrafish have provided key tools for morphological and physiological dissection of circuits and greatly extended understanding of their architecture. Here we discuss the startle circuit of fishes, with a focus on the Mauthner cells and associated interneurons called spiral fiber neurons and we add new observations on hindbrain circuit organization. We also briefly review and compare startle circuits of several other taxa, paying particular attention to how movement direction is controlled.